กระบวนการประกอบสร้างอุดมการณ์ในละครโทรทัศน์ไทยในช่วงภาวะวิกฤตทางการเมือง - พิมพร สุนทรวิริยกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
This study aimed at searching for and analyzing types of ideological themes in Thai television series and the processes that television program producers have used in reflecting ideology in these series during the political crisis. The study was conducted on 15 sampled television series aired from September 2006 to December 2007. The study found 16 ideological themes in Thai television series during the political crisis period. These include 2 political, 4 economic and 10 social and cultural ideologies as follows: Political ideologies: Nationalism and Authoritarianism Economic ideologies: Capitalism, Materialism/Consumerism, Monetarianism and Self-Sufficiency Social and Cultural ideologies: Social Classism Ideology, Feudalism, Patriarchy, Feminism, Localism, Buddhism, Occultism, Naturalism, Romanticism and Moralism. It was found that the dominant ideologies and counter ideologies appeared in the struggle between Capitalism, Materialism/Consumerism, and Monetarianism on one side, which were the principal ideologies; and Self-sufficiency and Localism, which were portrayed as opposing ideologies. Moreover, Classism, Capitalism, Materialism/ Consumerism and Monetarianism were frequently portrayed as causes of conflicts in the television series, with Romanticism eventually solving all conflicts. However, all the ideologies shown were controlled by Idealism, which governed the behaviors of all characters and therefore framed their different ideologies. All ideological beliefs held by the characters dictated their actions within the plot of the series. Ideological themes in Thai television series during the political crisis period were influenced by television stations in a position to control their inclusion with marketing ratings as the controlling factor. This was the controlling force of the television series, making them focus on love, greed, anger and obsession. These themes appeal to the audience as they are easy to understand and relate to. Television series managers are the persons in charge of setting the theme of the series. Their personal viewpoints, attitudes and experience are passed on to the scriptwriters who in turn create stories that contain the desired theme. The scripts are up-to-date and modern, having social and political crisis conditions as components, although ideologies expressed during the political crisis period such as economic Self-Sufficiency was presented only superficially to give the series a modern feel.